“DIFFERENTIATION OF TASKS IN MATHEMATICS LESSONS BASED ON THE EXPERIENCE OF PRESIDENTIAL SCHOOLS: A PRACTICAL MODEL BASED ON SCAFFOLDING” (Universal International Scientific Journal, 2026)
This article analyzes scaffolding as an effective approach to differentiating tasks inmathematics lessons. The study was conducted considering the diversity of students’ knowledge levelsand cognitive processing speeds in the context of general secondary schools. Within the practicalcomponent of the research, two versions of the same mathematical problem — a traditional (standard)format and a guided (scaffolded) format — were designed, and their impact on students’ problemsolving processes was observed.The scaffolded task model does not aim to simplify the problem itself but rather to deconstructcomplex cognitive processes into smaller, logically structured steps. Through this approach, studentsare guided on how to initiate problem-solving, select appropriate formulas, and construct solutions in acoherent and systematic manner. The findings indicate that guided tasks increase classroom engagementamong low-achieving students, reduce the number of unanswered responses, and support thedevelopment of written reasoning skills.The paper presents the theoretical foundations of scaffolding, an algorithm for reconstructingmathematical tasks, and practical recommendations for teachers. The proposed model can be directlyapplied by teachers working in general secondary schools, specialized educational institutions, andinternational curriculum contexts
Keywords: differential approach; scaffolding; task differentiation